Providing orbit information with predetermined bounded accuracy - Braun, Vitali (Logos Verlag Berlin, 2016)
The exchange of orbit information is becoming more important in view of the increasing population of objects in space as well as the increase in parties involved in space operations. The aim of this thesis was to investigate how orbit information maintained by a space surveillance system can be provided to its users. Services like collision avoidance require very accurate information, while other services might be less stringent. An approach was studied, which allows to derive orbit and covariance information of predetermined accuracy from a reference orbit. Using Chebyshev polynomials, continuous state vector and covariance matrix information can be provided. The major advantage is that no inter- or extrapolation on the user's side is required. A method to reduce the data amount by interpolating the variance envelope functions was also studied. The proposed method in this thesis gives access to highly accurate information from the catalogue, where this information is required. On the other hand it can also provide less accurate information, where requirements are less restrictive, thereby allowing for a significantly reduced amount of data to be transferred and stored.